2019
DOI: 10.1136/sextrans-2018-053949
|View full text |Cite
|
Sign up to set email alerts
|

Associations between vaginal bacteria implicated in HIV acquisition risk and proinflammatory cytokines and chemokines

Abstract: ObjectivesRecent studies have identified vaginal bacterial taxa associated with increased HIV risk. A possible mechanism to explain these results is that individual taxa differentially promote cervicovaginal inflammation. This study aimed to explore relationships between concentrations of bacteria previously linked to HIV acquisition and vaginal concentrations of proinflammatory cytokines and chemokines.MethodsIn this cross-sectional analysis, concentrations of 17 bacterial taxa and four proinflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…Past studies of the Zambian and Rwandan cohorts, as well as other studies, have shown that the presence of genital inflammation/ulceration increases an individual’s susceptibility to infection by HIV [ 3 , 4 , 6 9 , 19 , 20 ]. To test the possible role of genital inflammation or ulceration in the elevated biomarker profile, we compared the levels in individuals from the pre-infection group for whom any form of genital inflammation or ulceration had been reported in the 6 months prior to sample collection with those for whom no genital inflammation or ulceration was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies of the Zambian and Rwandan cohorts, as well as other studies, have shown that the presence of genital inflammation/ulceration increases an individual’s susceptibility to infection by HIV [ 3 , 4 , 6 9 , 19 , 20 ]. To test the possible role of genital inflammation or ulceration in the elevated biomarker profile, we compared the levels in individuals from the pre-infection group for whom any form of genital inflammation or ulceration had been reported in the 6 months prior to sample collection with those for whom no genital inflammation or ulceration was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Genital inflammation and ulceration clearly contributes to increased risk of HIV-1 acquisition. Studies in discordant couples in Rwanda and Zambia, as well as studies in other cohorts, have shown that individuals with genital ulceration/inflammation have a 5-10-fold higher risk for HIV infection [3][4][5][6][7][8][9][10]. Genital ulceration/inflammation has also been shown to affect the transmission bottleneck in heterosexual HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…had demonstrable cervicovaginal levels of HIV-1 [125]. Very recent research has focused on the identification of specific bacterial taxa in the vaginal niche and an increased HIV risk [126]. This analysis demonstrates associations between individual bacterial taxa and pro-inflammatory cytokines (tumor necrosis factor alpha (TNF-α) and interleukin (IL)-1β), suggesting that individual bacterial taxa might show an important role in determining the inflammatory state of the vagina and hence, an increased HIV risk [126].…”
Section: Bacterial Vaginosis and Sexually Transmitted Diseases (Stds)mentioning
confidence: 99%
“…Meanwhile, estrogen stimulates accumulation of glycogen in the vaginal epithelium, which is thought to play a major role in maintaining protective Lactobacillus-dominated microbiota (25). Secondly, disorder of the vaginal microbiome potentially leads to an increase in local inflammatory factors, such as interleukin-8 and tumor necrosis factor -a (27), which, along with a number of metabolites, trigger chronic systemic inflammation through the blood and lymph system, and in turn, affect the hypothalamic-pituitary-ovarian -E). Estimates are coefficients (b) from zero-inflated negative or standard negative binomial models.…”
Section: Discussionmentioning
confidence: 99%